PENGELOLAAN SAMPAH BERBASIS 3 R DESA MEKARJAYA KECAMATAN COMPRENG KABUPATEN SUBANG - Hirawan, Zaenal (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
Waste is an inseparable problem in community life. This is due to the still very conventional waste management model, which only moves waste from one place to another without further processing. Furthermore, people’s habits or habits that are less concerned about the surrounding environment when littering. Education for children, residents, and village officials is part of one solution to change people’s habits to care about waste. Meanwhile, waste management through the 3Rs is a form of high concern from all parties, especially the community. Through reduce, reuse, and recycle, it is hoped that the amount of waste can be reduced, because not all waste can be recycled. Making trash bins is a concrete form of reduce, reuse, and recycle waste, while also providing education that waste can still be useful for environmental sustainability. The form of the final community service activity is the creation of an information board that symbolizes the collaboration between the campus and the community in building an environmentally conscious village. Students not only convey information, but also create educational tools that can survive and develop independently within the community.